Exploring the global topology of the universe - Fagundes, Helio Vasconcelos [UNESP] (Sociedade Brasileira de Física, 2002)
We review the work done by our group on cosmic topology. It ranges from early atempts to solve a famous controversy about quasars thought the multiplicity of images, to quantum cosmology in this context and an application to QED renormalization.